Th17-associated cytokine gene hypomethylation reflects epigenetic dysregulation in graves’ disease - Jiang, Yanfei; Mu, Kaida; Huang, Zhaowei; Zhang, Xinwei; Wang, Yalin; Xu, Wenyu; Song, Ronghua; Zhang, Jinan (Frontiers in Immunology, 2025)
IntroductionGraves’ disease (GD) is an organ-specific autoimmune disorder characterized by the presence of thyroid-stimulating hormone receptor autoantibodies (TRAb), leading to hyperthyroidism. While genetic and environmental factors contribute to GD pathogenesis, the role of epigenetic mechanisms, particularly in regulating Th17-associated cytokines, remains poorly understood.MethodsThis study aimed to characterize the promoter methylation profiles of IL17, IL21, and IL22 in GD patients, evaluate their diagnostic potential, and explore correlations with clinical parameters. Targeted bisulfite sequencing was performed on peripheral blood mononuclear cells from 60 GD patients, including newly diagnosed and refractory individuals, and 60 matched healthy controls.ResultsSignificant hypomethylation at IL17, IL21, and IL22 promoter regions was observed in GD patients compared with controls (P = 2.5 × 10⁻⁷), with partial methylation restoration in refractory cases. Four specific CpG sites were identified as potential biomarkers, demonstrating good diagnostic performance with area under the curve (AUC) values exceeding 0.7, including chr4_123542549_R (AUC = 0.754) and chr12_68647247_R (AUC = 0.752). These sites were associated with elevated TRAb (OR = 4.00, P = 0.02) and FT4 levels (OR = 0.29, P = 0.02), respectively.DiscussionOur findings highlight Th17-related epigenetic dysregulation as a key feature of GD and support the potential of methylation markers for diagnostic and therapeutic monitoring applications.